2019
DOI: 10.30518/jav.553315
|View full text |Cite
|
Sign up to set email alerts
|

HFACS Analysis for Investigating Human Errors in Flight Training Accidents

Abstract: Training of pilots in civil aviation is the primary concern when dealing with accidents and incidents. There has been too little research into accidents during flight instruction. To advance the literature, the present study aims to analyze accidents during the instructional general aviation flights. This study examined investigation reports of 70 accidents involving instructional general aviation flights in the United States between 01.01.2018 and 12.12.2018. The accident data obtained from the National trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The health of pilots is an essential element in performing safety-related duties (Kilic & Soran, 2020) (Kilic, 2021b). Previous studies reported that adverse mental state of pilots gave rise to near-misses, incidents, and accidents (Kilic, 2019) , (Kilic, 2020) , (Havle & Kilic, 2019). Therefore, the mental state of aircrew is of paramount importance regarding safety in aviation (Kilic, 2021a) (Kilic & Ucler, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The health of pilots is an essential element in performing safety-related duties (Kilic & Soran, 2020) (Kilic, 2021b). Previous studies reported that adverse mental state of pilots gave rise to near-misses, incidents, and accidents (Kilic, 2019) , (Kilic, 2020) , (Havle & Kilic, 2019). Therefore, the mental state of aircrew is of paramount importance regarding safety in aviation (Kilic, 2021a) (Kilic & Ucler, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pilots are prone to making errors when they are ill (Johansson & Melin, 2018a) (Kilic, 2020a). There is an association between errors and adverse psychological and mental states of aircrew (e.g., sickness, stress, fatigue, loss of situational awareness and lack of vigilance) (Kilic & Gumus, 2020) (Kilic & Soran, 2019) (Kilic, 2022) Adverse physiological and mental states of the aircrew were attributed to 29% of training flight accidents (Kilic, 2019), 7% of air cargo accidents (Kilic & Gündogdu, 2020) and 16% of hot-air balloon accidents (Kilic, 2020b).…”
Section: Presenteeism and Aviationmentioning
confidence: 99%
“…When a student pilot performs a training flight with health issues (e.g., headache, stomachache, inner ear infection, flu, vestibular neuritis and motion sickness), there may be deterioration in concentration and an increase in stress level that may impede flight safety (Orford & Silberman, 2008). It has been already reported that impaired concentration poses a greater safety risk for student pilots, their colleagues and for their flight schools (Kilic, 2019). Furthermore, sick students may endanger their peers due to spread of disease and decline in performance .…”
Section: Presenteeism and Aviationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that several contributing factors including weather, system/equipment malfunction, human error, and organizational factors give rise to accidents and incidents in commercial aviation [10] as well as in general aviation [11]. Among these contributing factors, human error is associated with the largest portion of commercial air carrier accidents (more than 75%) [12][13] [14].…”
Section: Commercial Air Carrier Accidentsmentioning
confidence: 99%